Enhancing Productive Zakat Programs in Light of MaqÄá¹£id SyarÄ«’ah: Chance and Challenge in Contemporary Aceh - Mubarrak, Husni; Munir, Badrul; Achyar, Gamal (El-Barka, 2023)
Abstract: Introduction: As the main pillar of Islam, zakat is still convinced being an effective instrument in order to realize poverty alleviation and social equilibrium. Background Problems: This article discusses about implementation, challenge and moment that could be seized by Baitul Mal as an independent institution, to compile and distribute zakat in Aceh, after a broader jurisdiction that it has, to reduce poverty. However, the reality in Aceh currently shows that the poverty is still becoming the main broadly challenged social problems that faced. Research Method: This study is a qualitative one using semi-structured interviews with purposive sampling to stakeholders who are directly engaged in zakat management in Baitul Mal Aceh and other parties like academician and practician, as well as observation and documentation. Finding/Results: The finding of this research shows that as an independent board in Aceh province, Baitul Mal Aceh has a big chance and broader authority to maintain, manage and develop zakat based on Islamic sharia law in Aceh, although it has also many obstacles to realize it. This article suggests and proposes maqÄá¹£id syarÄ«’ah should be the parameter of any zakat programs conducted. By using maqÄá¹£id syarÄ«’ah, hopefully it could be the parameter of innovating and conducting any productive zakat programs for realizing a more welfare and beneficial (mashlahat) purposes.